2016
DOI: 10.1021/acs.langmuir.6b00053
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Phases of a Dipolar Perylene Derivative on Au(111) and Surface Potential Build-Up in Multilayers

Abstract: 9-(Bis-p-tert-octylphenyl)-amino-perylene-3,4-dicarboxy anhydride (BOPA-PDCA) is a strongly dipolar molecule representing a group of asymmetrically substituted perylenes that are employed in dye-sensitized solar cells and hold great promise for discotic liquid crystal applications. Thin BOPA-PDCA films with orientated dipole moments can potentially be used to tune the energy-level alignment in electronic devices and store information. To help assessing these prospects, we here elucidate the molecular self-asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 58 publications
1
14
2
Order By: Relevance
“…The tunneling current during scanning does not seem to affect the stable assemblies as there are no spontaneous changes in the assembly during scanning of the islands (Figure 3a−c). This is unlike the observation by Niederhausen et al, in which a dipolar perylene derivative (with a large dipole moment of 12 D) undergoes phase changes while scanning, 18 nor that of Li et al, in which hot electrons induce the formation of assemblies. 19 The dipole moment (2.1 D) of the terarylene is large enough to be influenced by the 3 V electric field induced 1 nm away but weak enough not to be affected during scans at −1 V when the tip is close to the surface.…”
Section: ■ Methodscontrasting
confidence: 79%
See 1 more Smart Citation
“…The tunneling current during scanning does not seem to affect the stable assemblies as there are no spontaneous changes in the assembly during scanning of the islands (Figure 3a−c). This is unlike the observation by Niederhausen et al, in which a dipolar perylene derivative (with a large dipole moment of 12 D) undergoes phase changes while scanning, 18 nor that of Li et al, in which hot electrons induce the formation of assemblies. 19 The dipole moment (2.1 D) of the terarylene is large enough to be influenced by the 3 V electric field induced 1 nm away but weak enough not to be affected during scans at −1 V when the tip is close to the surface.…”
Section: ■ Methodscontrasting
confidence: 79%
“…A couple of recent works come close to this, but the ordering of assemblies was induced by hot tunneling electrons. In one, the hot electrons coming from the STM tip to the surface were shown to induce surface phase changes of an assembly of a dipolar perylene derivative, 18 while, in another, transition from disordered to an ordered assembly was induced by injecting hot electrons onto the surface. 19 In this study, we investigate the formation of on-surface molecular networks of a diarylethene derivative.…”
Section: ■ Introductionmentioning
confidence: 99%
“…By nature, these comprise intramolecular polar bonds. Therefore, electrostatic dipole and multipole interactions play an important role in structure formation. , Likewise, hydrogen bonds can be a dominant factor in molecular self-assembly. , In addition to these interactions of permanent charges, mutual polarization and dispersion interactions contribute substantially. All of these are particularly important for molecules on solid surfaces such as metals, as the pairwise interaction magnitude may vary considerably for molecule–molecule and molecule–substrate. , Yet, predicting the self-assembled structure for a given material combination, based on a known molecular and substrate structure, remains one of the major challenges, as a reliable hierarchical ranking of the governing interaction energies based on empirical knowledge is not sufficiently possible.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few such studies have been reported for densely packed double layers grown using chiral molecules bearing twisted or helical backbones such as rubrene 63 and helices 64,65 under UHV condition and alkyl-substituted amino acid derivatives at the liquid/solid interface, 66 in contrast to much more abundant studies on self-assembled bi-and multilayer formation without specific registry through π-π stacking or dipolar interactions. [67][68][69][70][71] For porous bilayer networks grown by self-assembly of acyclic building blocks, chirality did not take part, since only achiral bilayers were known. 72,73 In this connection, to shed light on the possibility of stereocontrolled epitaxial growth of porous SAMNs, we designed cDBA-OC6-OH(S) and its enantiomer cDBA-OC6-OH(R) (Chart 1) bearing hydroxy groups at the stereogenic centres.…”
Section: Stereospecific Epitaxial Growthmentioning
confidence: 99%